Comprehensive assessment of SARS-CoV-2 antibodies against various antigenic epitopes after naive COVID-19 infection and vaccination (BNT162b2 or ChAdOx1 nCoV-19) - Lee, Jihyun; Lee, Dong-Gun; Jung, Jin; Ryu, Ji Hyeong; Shin, Soyoung; Cho, Sung-Yeon; Lee, Raeseok; Oh, Eun-Jee (Frontiers in Immunology, 2022)
Comprehensive assessment of SARS-CoV-2 antibodies against antigenic epitopes and cross-neutralization on variants is essential to monitor after infection or vaccination. From 32 COVID-19 patients and 40 vaccinated individuals (20 Oxford–AstraZeneca (AZ) and 20 Pfizer–BioNTech (BNT)), 348 serial sera are collected until 40 days after infection and 3 months after homologous booster vaccination. Antibody levels were monitored using a multiplex-bead assay including variant spike antigens, Roche (S1/RBD total) and a surrogate virus neutralization test (GenScript). Anti-S/S1/RBD levels were higher than anti-S2/N levels from 2 weeks after infection and were higher in severe infection (P < 0.05). Vaccination showed highest antibody levels after 1-month booster and had consistently high levels in the order of anti-full S, anti-RBD, anti-S1 and anti-S2. Infection induced higher anti-S2/N levels than prime vaccination (P < 0.05). Three months after BNT/BNT vaccination, antibody levels against S1/RBD and 23 variant antigens were higher than post-infection or AZ groups (P < 0.05). Regarding intraindividual changes from post-prime to post-boost vaccination, boost induced a 1.1- to 3.9-fold increase on multiplex-bead assay, 22.8- to 24.2-fold on Roche assay and 22.8- to 24.2-fold on GenScript assay. Post-prime levels by multiplex-bead assay predicted post-boost levels, but Roche and GenScript results were not predictive in the AZ group. The kinetics of SARS-CoV-2 antibody levels vary depending on the antigenic epitopes, assay kit, disease severity or vaccine type. Assessing seroconversion using multiplex-bead assays may contribute to monitoring the disease course, adjusting vaccination strategies, and accelerating vaccination efficacy.